Faktor-Faktor Yang Berhubungan Dengan Konsumsi Mi Instan Pada Mahasiswa Gizi Universitas Binawan: Factors Related To Consumption Of Instant Noodles In Nutrition Students Of Binawan University - Hardiati, Riski Amilia; Istianah, Isti (Jurnal Pangan Kesehatan dan Gizi Universitas Binawan, 2024)
Increased consumption of processed foods, including instant noodles, which have excess sodium content, can make a significant contribution to non-communicable diseases. The purpose of this study was to analyze the factors associated with the consumption of instant noodles in nutrition students at Binawan University. This study used a cross-sectional design involving 76 nutrition students at Binawan University. Data were analyzed using Chi-square test. The research subject data for consumption of instant noodles was the most rare category, namely 46 people (60,5%), nutritional knowledge was in the poor category, namely 50 people (65,8%), the influence of peers in the affected category was 47 people (61,8%), the length of use of social media in the old category is 48 people (63,2%), pocket money in the low category is 45 people (59,2%), the availability of instant noodles in the easy category is 63 people (82,9%). Statistical data showed that there was a relationship between instant noodle consumption and the influence of peers, pocket money, and availability of instant noodles (p<0,05). There is no relationship between nutritional knowledge and duration of use of social media (p>0,05). There is a relationship between the consumption of instant noodles with the influence of peers, allowance, and the availability of instant noodles.